Rapid Detection of Microorganisms by Automated Blood Culture System: Experience of 3220 cases of Blood Culture (Bangladesh Journal of Infectious Diseases, 2023)
Background: Blood culture is important for diagnosis of various diseases and isolation of micro-organisms.Objective: The purpose of the present study was to assess the rapid detection of microorganisms by automated blood culture system.Methodology: This retrospective study was conducted in the Department of Microbiology at Dhaka National Medical College, Dhaka, Bangladesh and IBN Sina D. Lab & Consultation center, Doyagonj, Dhaka, Bangladesh from January 2020 to December 2020 for a period of one year. All the patients presented with suspected cases of blood stream infection were selected as study population. Blood samples were collected from suspected cases.Results: A total of 3220 blood samples were collected from patients. Among them, bacteria were isolated 372(11.55%) cases. The most common isolated organisms were Salmonella typhi 276(74.2%), Salmonella paratyphi A 52(14%), Escherichia coli 21(5.6%), Pseudomonas species 14(3.8%), and Staphylococcus aureus, 9(2.4%). Salmonella typhi is the most common organisms and showed sensitivity pattern to imipenem 97.82% colistin 88.41%, amikacin 76.81% and ciprofloxacin 49.28%.Conclusion: In conclusion Salmonella typhi, Salmonella paratyphi A and Escherichia coli are the most common isolated bacteria from the blood stream infection.Bangladesh Journal of Infectious Diseases, June 2022;9(1):3-6